The Unclear Status of The Suspect in the Investigation Stage: Case Study of The Extension of The Cooperation Agreement on The Management and Operation of The Jakarta International Container Terminal - Okpirianti, Reni; Santoso, Topo; Nasriana, Nasriana (Walisongo Law Review (Walrev), 2022)
Unclear status of the suspect in the investigation stage for the suspect even though it is not yet legally available that he is found guilty: What is the cause of the unclear status of the suspect at the investigation stage (case study of extension of the Cooperation Agreement for the Management and Operation of the Jakarta International (JICT) Terminal? or what are the legal consequence and what actions must be taken for the pending case at the investigation stage (adjudication) the purpose of the study is to find out the cause of the unclear status of the suspect at investigation stage and to find out and clary the legal consequences and actions to be taken on cases that are hanging at investigation stage (adjudication) by someone who has unclear suspect status on himself. The legal research methodology is a dogmatic study or doctrinal research. The cause of the unclear status of the suspect in the extension of the JICT Operation and Management Cooperation Agreement, the value of state losses as a result of the investigation reported by BPK, 1b. Remain in doubt. The Attorney General does not believe that there is a state loss in the JICT, Management Contract Extension All Procedure according to the rules have been carried out by suspect. The legal consequences for unclear status of the suspect are very detrimental to the suspect and injure the basic right of citizens to legal certainty and justice, 3b. The abuse of authority of the apparatus results in human right violations.3c. The legal action to be taken by the suspect is. Protection may be requested through a pre-trial which guarantees the rights of the suspect in accordance with his dignity as a human being. The termination of the investigation of the suspect may refer to the provisions of article 76 of the regulation of the National Police Chief No. 14 of 2012 concerning the management of criminal cases. Ketidakjelasan status tersangka dalam tahap penyidikan (pra ajudikasi), membawa konsekuensi hukum tersendiri bagi tersangka walaupun secara yuridis belum ada kepastian dinyatakan bersalah: Apakah penyebab ketidakjelasan status tersangka pada tahap penyidikan (studi kasus Perpanjangan Perjanjian Kerjasama Pengelolaan dan Pengoperasian Jakarta International Center Terminal (JICT)? atau Apakah akibat hukum dan tindakan apa yang harus dilakukan atas  perkara yang menggantung di tahap penyidikan (ajudikasi).Tujuan penelitian adalah, untuk mengetahui penyebab ketidakjelasan status tersangka dan untuk mengetahui dan memperjelas akibat hukum dan tindakan yang harus dilakukan atas perkara yang menggantung di tahap penyidikan (ajudikasi). Penelitian ini adalah penelitian hukum dengan studi dogmatik atau doctrinal research. Hasil penelitian menunjukkan bahwa penyebab ketidakjelasan status tersangka pada kasus Perpanjangan Perjanjian Kerjasama Pengelolaan dan Pengoperasian JICT, masih diragukan nilai kerugian negara hasil investigatif yang dilaporkan oleh BPK. Jaksa Agung tidak meyakini adanya kerugian negara dalam perpanjangan kontrak pengelolaan JICT. Semua prosedur sesuai aturan telah dilakukan oleh tersangka. Akibat hukum atas ketidakjelasan status tersangka sangat merugikan tersangka dan mencederai hak dasar warga negara untuk kepastian hukum dan keadilan. Atas penyalahgunaan wewenang aparat tersebut, berakibat pelanggaran hak asasi manusia (HAM). Tindakan hukum yang harus dilakukan oleh tersangka adalah dapat dimintakan perlindungan melalui pranata pra peradilan yang akan menjamin hak-hak tersangka sesuai dengan harkat dan martabatnya sebagai manusia atas penghentian penyidikan, tersangka dapat mengacu pada aturan Ketentuan Pasal 76 Peraturan Kapolri No. 14 Tahun 2012 tentang Manajemen Perkara Pidana.